An Analytical Study of Tools and Techniques for Movie Marketing - Guptha, Ch. Abhinav; Maik, Garima (The Asian Journal of Technology Management (AJTM), 2014)
Abstract. Bollywood or Hindi movie industry is one of the fastest growing sector in the media and entertainment space creating numerous business and employment opportunities. Movies in India are a major source of entertainment for all sects of society. They not only face competition from other movie industries and movies but from other source of entertainment such as adventure sports, amusement parks, theatre and drama, pubs and discothèques. A lot of man power, man hours, creative brains, and money are put in to build a quality feature film. Bollywood is the industry which continuously works towards providing the 7 billion population with something new always. So it is important for the movie and production team to stand out, to grab the due attention of the maximum audience. Movie makers employ various tools and techniques today to market their movies. They leave no stone unturned. They roll out teasers, First look, Theatrical trailer release, Music launch, City tours, Producer’s and director’s interview, Movie premier, Movie release, post release follow up and etc. to pull the viewers to the Cineplex. The audience today which comprises mainly of youth requires photos, videos, meet ups, gossip, debate, collaboration and content creation. These requirements of today’s generation are most fulfilled through digital platforms. However, the traditional media like newspapers, radio, and television are not old school. They reach out to mass audience and play an upper role in effective marketing. This study aims at analysing these tools for their effectiveness. The objectives are fulfilled through a consumer survey. This study will bring out the effectiveness and relational importance of various tools which are employed by movie marketers to generate maximum returns on the investments by using various data reduction techniques like factor analysis and statistical techniques like chi-square test with data visualization using pie charts. Keywords: Movie promotion, movie marketing, digital marketing, marketing tools, Bollywood, marketing techniques